Implementation of Forensic Nursing in Emergency Departments: An Exploratory Qualitative Study - Rahmah Yanita Kusuma; Ariani Arista Putri Pertiwi; Christantie Effendy; Syahirul Alim; Sri Setiyarini (Fakultas Ilmu-ilmu Kesehatan, 2026)
Forensic nursing is a new field that has yet to be widely recognized in Indonesia. Despite the high crime rate and the large number of forensic case patients who come to the emergency department (ED), there are still no specific regulations governing such cases. This study aims to explore the application of forensic nursing in EDs in Yogyakarta. A qualitative exploratory study was conducted. The researchers conducted in-depth semi-structured interviews in the EDs of government and private hospitals in Yogyakarta Province, Indonesia. The participants were 12 ED nurses who handled forensic cases. Triangulation was conducted through interviews with two ED head nurses and three security staff, as well as a review of medical records. The data analysis comprised identifying meaning units, conducting initial and refined coding, grouping them into categories, and generating themes using the forensic nursing paradigm approach. This study identified the following themes: (1) forensic nursing cases, (2) nursing roles and responsibilities in forensic cases, (3) the significance of crime evidence, (4) forensic nursing implementation support, and (5) challenges and needs in implementing forensic nursing. This study found that forensic nursing has been implemented in Eds in Yogyakarta. However, it has not been effectively executed.